AN ANALYSIS OF VERBAL AND NON-VERBAL COMMUNICATION CAPABILITY OF ONE AUTISTIC SUFFERERS AT SEDAYU - Anik Astuti; Widyashanti Kunthara Anindita (Translation and Linguistics (Transling), 2023)
This study uses a study of linguistics from the point of view of psycholinguistics. This study aims to determine the analysis of verbal and non-verbal communication in one autistic sufferers in Sedayu Village.The research method used in this research is a descriptive qualitative research method and involves collecting data using observation and interview techniques. The theory used in this study is the theory of Leonard Bloomfield (1877-1949). This theory is a series of stimuli and responses that highlight verbal and non-verbal language behavior.This research is a field research that was conducted on March 11, 2022, March 13, 2022, March 15, 2022, and March 17, 2022 in Sedayu Village and obtained fourteen data points from various kinds of questions given to one autistic sufferers during observation and interviews. In this study, it was found that one of the autistic sufferers was observed to be able to communicate verbally, even though it was only one to two words and non-verbally, but not as well as normal people.